Proximal arterial cannulation in thoracic aortic surgery—Literature review. Issue 7 (18th June 2019) - Harky, Amer; Oo, Shwe; Gupta, Shubhi; Field, Mark
Abstract: Surgery on thoracic aorta is complex with a number of approaches being required depending on the pathology and anatomy that is specific to each patient and therefore, careful planning is required to ensure successful outcomes. Among the key factors that determine a satisfactory and safe operation is the choice of arterial cannulation site to establish cardiopulmonary bypass and deliver brain protection adequately. Direct proximal aortic cannulation is the gold‐standard method for elective aortic root surgery and traditionally femoral arterial cannulation has been used in complex aortic surgeries such as redo or acute pathologies; however, axillary and innominate artery (IA) cannulation has evolved dramatically and several centers are currently using proximal cannulation sites as the default cannulation choice in elective and emergency settings of complex thoracic aortic surgeries. The evidence behind cannulating the IA is growing; however, it is yet to be well established through large studies or trial to confirm its superiority to other methods of central cannulation techniques.